New Lower Bounds for the Constants in the Real Polynomial Hardy–Littlewood Inequality. (2nd August 2016) - Cavalcante, W.; Núñez-Alarcón, Daniel; Pellegrino, D.
ABSTRACT: In this article, we obtain new lower bounds for the constants of the real scalar-valued Hardy–Littlewood inequality for m -homogeneous polynomials on spaces when p = 2 m and for certain values of m .